Analisis Data Panel Dalam Memprediksi Faktor Determinan Kemiskinan di Provinsi Kalimantan Selatan - Fatekhatul Hasni Nur Fadila; Najla Hikmalia Dhiyaa Ulhaq; Riziq Apani Khoir; Sulthon Muhammad Al Fatih (PPJP Universitas Lambung Mangkurat, 2023)
This research aims to understand the level of poverty and the elements that influence the level of poverty in the Province of South Kalimantan. The data used is secondary data sourced from the Satu Data Banua website for South Kalimantan Province, a combination of cross-sectional data from 13 regencies/cities in South Kalimantan Province with time series data from 2017 to 2021. This research uses three independent variables and one dependent variable consisting of the Open Unemployment Rate (X1), Gini Ratio (X2), and Life Expectancy Rate (X3) as well as the Percentage of Poor Population as (Y). The panel data analysis method is carried out by conducting model selection tests on the Common Effect, Fixed, and Random Effects Models to determine the best model in panel data estimation. The results showed that the random effect model found that the open unemployment rate and life expectancy had a significant effect. In contrast, the Gini ratio did not affect the percentage of poor people in South Kalimantan Province. Based on the hypothesis test, simultaneously (simultaneously), the three independent variables significantly affect the percentage of poverty in South Kalimantan Province.